Teaching a Bilingual Class for Lower Primary Level: Challenges and Strategies - Armand, Suci Utami; Gandana, Isti Siti Saleha (UICELL, 2023)
Bilingual education is a system of education that uses two languages as classroom instruction. The demand for bilingual schools has increased quite significantly in Indonesia. Yet, bilingual teachers often face challenges in teaching bilingual classes especially those teaching at lower primary level. This study seeks to understand a teacher’s challenges and strategies in teaching a bilingual class. Adopting a qualitative case study with a first-grade primary school teacher as the participant, data were obtained through semi-structured interviews. The findings indicated two major kinds of challenges: internal and external. Similarly, the strategies adopted corresponded two the teacher’s internal and external motivations. This study suggests that bilingual teachers need to be provided with ample guidance and supervision in their bilingual classroom practice in order to create impactful learning. Further, collaboration between the school, teachers and parents is also necessary for the program to run smoothly. Keywords: bilingual education, lower primary level, teacher’s challenges, and strategies